2016
DOI: 10.1038/srep32656
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Drp1 mitochondrial translocation provides neural protection in dopaminergic system in a Parkinson’s disease model induced by MPTP

Abstract: Accumulating evidence suggest mitochondria-mediated pathways play an important role in dopaminergic neuronal cell death in Parkinson’s disease (PD). Drp1, a key regulator of mitochondrial fission, has been shown to be activated and translocated to mitochondria under stress, leading to excessive mitochondria fission and dopaminergic neuronal death in vitro. However, whether Drp1 inhibition can lead to long term stable preservation of dopaminergic neurons in PD-related mouse models remains unknown. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 68 publications
3
97
0
Order By: Relevance
“…Dominant-negative inhibition of Drp1 in a PINK1 −/− mouse-knockout model of PD, as well as in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism in mice, prevented neuronal death and rescued the impaired dopamine release that is associated with PD (Rappold et al, 2014). More recent work on the MPTP mouse model of PD supports these findings, as p110-TAT-peptidemediated inhibition of Drp1 localization to mitochondria attenuated the death of dopaminergic neurons (Filichia et al, 2016).…”
Section: Mitochondrial Dynamics In Neurodegenerative Diseasessupporting
confidence: 63%
See 1 more Smart Citation
“…Dominant-negative inhibition of Drp1 in a PINK1 −/− mouse-knockout model of PD, as well as in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism in mice, prevented neuronal death and rescued the impaired dopamine release that is associated with PD (Rappold et al, 2014). More recent work on the MPTP mouse model of PD supports these findings, as p110-TAT-peptidemediated inhibition of Drp1 localization to mitochondria attenuated the death of dopaminergic neurons (Filichia et al, 2016).…”
Section: Mitochondrial Dynamics In Neurodegenerative Diseasessupporting
confidence: 63%
“…Drp1 has been put forward as a drug target for preventing mitochondrial fragmentation under diverse pathological conditions (Rosdah et al, 2016). Indeed, currently available Drp1 inhibitors have shown neuroprotective properties in animal models of HD (Guo et al, 2013b), PD (Hatch et al, 2014;Filichia et al, 2016) and ischemic stroke (Grohm et al, 2012;Li et al, 2015;Zhang et al, 2013). However, given the widespread expression of the fission enzyme and the detrimental consequences on the development and function of the nervous system upon deletion of Drp1, targeting neuron-specific regulators of Drp1 or other components of the mitochondrial fission/fusion machinery are potentially safer therapeutic strategies.…”
Section: Resultsmentioning
confidence: 99%
“…DLP1 has been proposed forward as a treatment target for preventing mitochondrial fragmentation under various pathological conditions (Guo et al ., 2013; Zhang et al ., 2013; Filichia et al ., 2016; Kim et al ., 2016). The DLP1 mitochondrial fission/fusion machinery as a therapeutic target of prion diseases warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Lyophilized peptides are stored at −80 °C freezer and are dissolved in sterile water before use. P110 has shown efficacy and no toxicity both in vitro and in animal models in vivo (Filichia et al, 2016; Guo et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…In our previous study we have found that P110 treatment in the dosage of 0.5–3 mg/kg/day range were effective in a Huntington’s disease mouse model (Guo et al, 2013), Parkinson’s disease mouse model (Filichia et al, 2016) and ischemic brain injury in rat (Guo et al, 2014). We tested the dosages of P110 at 0.5 and 1.0 mg/kg/day in our MS mouse model and found that P110 at 1.0 mg/kg/day provided better protection.…”
Section: Methodsmentioning
confidence: 99%